The Effect of Technology Adaptation and Government Financial Support on Sustainable Performance of MSMEs during the COVID-19 Pandemic - - Kurniawan; Agung Maulana; Yusuf Iskandar (Cogent Business & Management, 2023)
By observing 1026 samples of Indonesian MSMEs, this study tries to explain the effect of technology adaptation, innovative financial practices, and financial policy-related factors on sustainable financial performance and the survival-recovery of MSMEs during the Covid-19 pandemic. Data were analyzed using the PLS-SEM technique through SMARTPLS software version 3. Samples were selected and collected through purposive sampling by setting criteria and deploying them online and offline. The results show that the agility to conduct technology adaptation and innovative financial practices by MSMEs significantly affected their sustainable financial performance during the COVID-19 pandemic. Innovative financial practices also positively moderate the relationship between technology adaptations on sustainable financial performance. On the other side, preferential policies of the bank have a significant impact on sustainable financial performance directly and indirectly through the mediating role of perceived policy effectiveness. The financial support by the government also significantly affected the sustainable financial performance of MSMEs through the mediating role of perceived policy effectiveness. Eventually, sustainable financial performance significantly affected the survival-recovery of MSMEs.
Keywords: E5; G4; L26; 650; Crisis Management; MSMEs; Policy-related Factors; Sustainable Finance; Technology Adaptation